ANALISIS SISTEM PUSAT KEWILAYAHAN KABUPATEN LAMPUNG SELATAN - Verlina Agustine; Fuady, Shahnaz Nabila; Wijayanti, Goldie Melinda; Tanjung, Adinda Sekar; Rilansari, Valendya (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
Roads play an important role in achieving national development goals, particularly in ensuring equitable development across regions with potential for growth at both regional and national levels. Lampung Province serves as the gateway to Sumatra Island, connecting various other provinces on the island to Java. The province is actively developing its regional potential, especially in the agriculture and plantation sectors. A large portion of these promising sectors, particularly in agriculture and plantations, is concentrated in three regencies: Way Kanan, Tulang Bawang Barat, and North Lampung. To support the development plans of these highly potential regions, the Lampung Provincial Government plans to improve and upgrade road infrastructure in order to boost economic development. This study identifies the financial feasibility of improving and upgrading provincial road infrastructure in Way Kanan, Tulang Bawang Barat, and North Lampung Regencies by using spatial analysis and quantitative analysis of financial feasibility criteria, including calculations of Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period. Based on the analysis, the most feasible alternative road route for development is the Simpang Tulung Randu – Adijaya – Tajab – Sp. Soponyono – Serupa Indah – Negara Ratu – Kotabumi and Serupa Indah – Bumiharjo – Sp. Way Tuba section. Road 1 has the highest IRR at 7.92%, the highest NPV at IDR 614,905,153,799, the highest PI at 2.30, and the fastest Payback Period of 13 years, 9 months, and 11 days.